Analysis of medical tourism policy: a case study of Thailand, Turkey and India - Abdul Manaf, Rosliza; Juni, Muhamad Hanafiah; A. H., Hafizan; O., Mardiana; B., Sahar; M. R., Jacinta; S. S., Syafiq (Community Health Society Malaysia, 2018)
Background: Medical tourism has gained popularity for the past 15 years and formulating the best medical tourism policy is challenging. This article performs a comparative analysis of health policies related to medical tourism in three developing countries which are India, Thailand and Turkey. Health policy triangle is used to better understand the policy studied and the potential implications of medical tourism policy to the aforementioned countries identified by the analysis are presented. Materials and Methods: A scoping review was done related to medical tourism policies frameworks and their implications in India, Thailand, and Turkey. The primary search was conducted using public and journal search engines. Articles were screened for relevant titles and abstracts, followed by a detailed examination of the full texts, applying defined inclusion and exclusion criteria. Articles that fulfilled those criteria were used in this comparative analysis study. Result: Based on the analysis, these countries formulated their policy plans to address their continuously growing medical tourism sector. In the formulation process, the actors aimed for the policies to exert influence at a local, national, regional or international level. In India, Thailand and Turkey, economic drive is one the major factors that have driven them to be actively promoting medical tourism industries. Each policy needs were forecasted and targets were defined in the process of formulating the health policies. The policies were then implemented accordingly. All the essential components of the health policy development process and the impact of the policies are discussed in depth in this article. Conclusion: The medical tourism policy processes in Thailand, Turkey and India are well developed in terms of problem definition, policy formulation and implementation of policies. However, there is no appropriate platform to evaluate in order to identify the effectiveness and pitfalls throughout the stages of a health policy cycle. These policies have generated national incomes but not necessarily add value for local people whereby the return investment may not be invested to improve local healthcare system.